Fluidization of granular media wetted by liquid He4 - Schröter, Matthias; Herminghaus, Stephan; Huang, Kai; Sohaili, Masoud (Physical Review E, 2009)
We explore experimentally the fluidization of vertically agitated polymethylmethacrylate spheres wetted by liquid He4. By controlling the temperature around the λ point, we change the properties of the wetting liquid from a normal fluid (helium I) to a superfluid (helium II). For wetting by helium I, the critical acceleration for fluidization (Γc) shows a steep increase close to the saturation of the vapor pressure in the sample cell. For helium II wetting, Γc starts to increase at about 75% saturation, indicating that capillary bridges are enhanced by the superflow of the unsaturated helium film. Above saturation, Γc enters a plateau regime where the capillary force between particles is independent of the bridge volume. The plateau value is found to vary with temperature and shows a peak at 2.1 K, which we attribute to the influence of the specific heat of liquid helium. © 2009 The American Physical Society.